SURVEI INTEGRITAS AKADEMIS DAN NON-AKADEMIS PADA MAHASISWA - Rosidah A; Amia Luthfia (Communicare : Journal of Communication Studies, 2016)
Students are one of the main targets of anticorruption campaign conducted by KPK (Corruption Eradication Commission) in Indonesia. It is because they are considered as a group that is able to influence other groups in the community in order to understand and instill the anticorruption values. They are also considered as a group of educated people who have high idealism and criticism. However, sometimes it is found that students have done dishonesty practices, no disciplines, or they are not concerned with what is happening around them, and so forth. Therefore, it is important to study how far the students understand the anticorruption values, specifically to learn their attitudes toward academic dishonesty (such as cheating, plagiarism, breaking class rules, etc.), non-academic integrity, such as students’ lifestyle and their understanding to the obligation as students, and their concern about corruption practices in Indonesia. It is expected that the result can provide valuable inputs for the initiator of anticorruption campaign in Indonesia, in this case KPK, in conducting a campaign to the students. The methodology is quantitative approach by using a survey to students as the respondents. Data analysis uses descriptive analysis, which is the frequency distribution. The scope is limited to the students of Binus University and attitudes as the variable. The results show that in terms of affection and cognition, they are aware that the fraudulent practices should not be performed and they also do not like the actions. However, as in conative (behavior) there is still tendency that some students are doing it. The respondents are aware to avoid hedonism and are concerned about the number of corruption cases prevailing in Indonesia and they support the appropriate punishment for the corruptors. As the suggestion for further research, it should be expanded to a wider scope of study. The variable of academic dishonesty can also be specified according to field of study. Keywords: Students, attitude, integrity, anticorruption campaign Mahasiswa adalah salah satu target utama kampanye antikorupsi KPK (Komite Pemberantasan Korupsi) di Indonesia. Hal ini karena mereka dianggap mampu mempengaruhi kelompok lain dalam masyarakat untuk memahami dan mengamalkan nilai antikorupsi. Selain itu, mereka dianggap sebagai kelompok masyarakat terpelajar yang memiliki idealisme dan sikap kritis yang tinggi. Akan tetapi, praktik-praktik ketidakjujuran, tidak disiplin, tidak acuh terhadap situasi di sekitarnya kerap terlihat dilakukan mahasiswa. Untuk itu, penelitian ini ingin mempelajari seberapa jauh mahasiswa memahami nilai-nilai antikorupsi dan integritas mereka. Secara spesifik bagaimana sikap mereka terhadap praktik kecurangan akademis yang terjadi di kampus, dan juga pada bidang non-akademis, seperti gaya hidup dan pemahaman tugas sebagai mahasiswa, serta perhatian mereka terhadap korupsi di Indonesia. Hasil penelitian diharapkan dapat menjadi masukan bagi inisiator kampanye antikorupsi dalam berkomunikasi kepada mahasiswa, terutama dalam melakukan pendidikan antikorupsi. Metode penelitian yang digunakan adalah kuantitatif dengan metode survei kepada mahasiswa sebagai responden. Analisis data menggunakan analisis deskriptif, yaitu Abstrak 37 38 Rosidah & Amia Luthfia SURVEI INTEGRITAS AKADEMIS DAN NON-AKADEMIS PADA MAHASISWA distribusi frekuensi. Ruang lingkup penelitian dibatasi pada responden mahasiswa di Binus University dan variabel sikap. Hasil penelitian didapatkan bahwa dari segi kognisi dan afeksi kebanyakan responden mengetahui bahwa kecurangan akademis tidak sepatutnya dilakukan dan mereka tidak menyukai hal tersebut. Namun masih ada kecenderungan (aspek perilaku) pada sebagian mahasiswa untuk melakukan kecurangan akademis. Responden juga berusaha untuk menghindari gaya hidup bermewah-mewahan dan mereka memiliki kepedulian terhadap masalah korupsi di Indonesia dan mendukung hukuman yang setimpal bagi koruptor. Saran bagi penelitian selanjutnya adalah dapat diperluas ruang lingkup penelitian dan variabel integritas akademis dapat dispesifikkan lagi sesuai bidang ilmu. Kata kunci: Mahasiswa, sikap, integritas, kampanye antikorupsi